2022
DOI: 10.1007/s40821-021-00199-5
|View full text |Cite
|
Sign up to set email alerts
|

University spillovers, absorptive capacities, and firm performance

Abstract: This study investigates the impact of both university spillovers and firms’ absorptive capacities on firms’ financial performance, using a multilevel approach. Considering internal firm characteristics as well as external regional characteristics, our results clearly show that university spillovers do not have a per se stimulating effect. It is the interaction between firms’ absorptive capacities and local university spillovers, which proves to have a positive and significant effect on firms’ economic performa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 144 publications
(158 reference statements)
2
11
0
5
Order By: Relevance
“…However, Goliaths, although less ambitious for environmental and social purposes, according to the authors, react to Davids by engaging in sustainable corporate activities. Thus, our findings send a signal that emerging small firms demand stronger attention and support from the policymakers, especially through financial instruments, to reach sustainability goals, similarly expressed in the article of Lehmann et al (2022). In result, internal R&D and IP in‐licensing are likely to be the main sources for firms developing new technology that creates sustainable innovation.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…However, Goliaths, although less ambitious for environmental and social purposes, according to the authors, react to Davids by engaging in sustainable corporate activities. Thus, our findings send a signal that emerging small firms demand stronger attention and support from the policymakers, especially through financial instruments, to reach sustainability goals, similarly expressed in the article of Lehmann et al (2022). In result, internal R&D and IP in‐licensing are likely to be the main sources for firms developing new technology that creates sustainable innovation.…”
Section: Discussionsupporting
confidence: 70%
“…Moreover, the sample was biased, as it was gathered from economic sectors active in eco‐innovation, thus, not providing the necessary validity. Further, our negative finding can be explained by the research of Arnold (2017) and (Lehmann et al, 2022) who demonstrated that sustainability knowledge per se is not sufficient for firms to develop sustainable products and services. Although firms source new knowledge and technology from universities to improve their innovation performance, the focus of this collaboration is not sustainability issues, and university spillovers do not have a per se stimulating effect on firms.…”
Section: Discussionmentioning
confidence: 78%
“…The development of TH is primarily influenced by the regional adoption of novel products, goods, services and technologies with a strong need for the capacity to absorb foreign knowledge spillovers (Lehmann et al, 2022). Consequently, industries maintain their technological innovation leadership.…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…University research output, an important source of knowledge spillovers, plays a crucial role in the USOs creation [37]. Firms strategically invest in their absorptive capacity to exploit knowledge spillovers from external sources and turn this information inflow into a competitive advantage [38].…”
Section: The Role Of Public Entrepreneurial Universities In the Unive...mentioning
confidence: 99%
“…The limitations of the study are: measuring knowledge spillovers by focusing on knowledge provided by the public sector does not capture the total amount of potential local knowledge flows; private sector research activities generate knowledge spillovers that should ideally also be considered; the multilevel approach is based on a rather small unbalanced panel, which is not ideal as larger sample sizes could substantiate the recommendations derived from the results; and further control variables could be included in the analyses. [82] The research approach used in this article was based on theoretical sampling, where the analysis of two case studies was expected to fertilize and substantiate the understanding of the five models of third mission activities…”
Section: Research Approachmentioning
confidence: 99%